which two expressions are equivalent.
![which two expressions are equivalent class=](https://us-static.z-dn.net/files/d3a/f8e3a2fee0967a39800094210c1f124e.jpg)
Answer:
C and D
Step-by-step explanation:
It is the same but its reversed in the parentheses, so they are equivalent.
Answer: C and D
Step-by-step explanation: SO what you need to do here is pick any number to plug in as y let’s say 2. 7+(5*2)=17 and then you solve for the next equation using 2. (7+5)*2=24. Now we know its not a. Let’s do b (12-4)*2=16 and 12-(4*2)=4 that can’t be it. Now c 8+(2*3)=14 and 8+(3*2)=14. Now D (11/2)+6=11.5 and 6+(2/11)= 11.5. You can use any number to plug in.